WS2 nanoparticle-decorated, vertically aligned SnS2-based high-performance heterostructures for ambient-stable ultrafast photodetection - Das, Chayan; Kumar, Suresh; Sharma, Anjali; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2025)
The development of visible-light photodetectors with high responsivity, rapid response, and long-term ambient stability remains a critical challenge in optoelectronics. Here, we report a high-performance photodetector based on a vertically aligned SnS2 film interfaced with WS2 nanoparticles, forming a p-n heterojunction. This device is fabricated using a scalable two-step method-chemical vapor deposition (CVD) for SnS2 growth and solution-based drop-casting for WS2 deposition-enabling precise control over the heterointerface, but trap states are inevitable due to the use of thermal CVD and the drop-casting method. The resulting photodetector exhibits remarkable optoelectronic characteristics, including a responsivity of 0.76 A/W, a detectivity of 7.56 x 10(11) Jones, a photo-to-dark current ratio of 119, and a fast rise time of 0.297 ms under visible illumination. These performance metrics are directly attributed to the optimized heterointerface, where the built-in electric field at the nanoscale WS2/SnS2 junctions promotes efficient charge separation and minimizes recombination losses. Notably, the device retains over 95% of its initial performance even after 1 week of ambient exposure, highlighting its superior environmental robustness. This work introduces an interface-engineering strategy that leverages the unique electronic properties of earth-abundant, nontoxic two-dimensional materials, offering a viable pathway for scalable, high-speed, and stable photodetectors suitable for next-generation optoelectronic systems.
Keywords: 2D; CVD; heterojunction; photodetector; SnS2; WS2